Social Skills’s Analysis of Elementary Students in Strengthening Implementation of Character Education (Journal of Primary Education, 2017)
Based on the results of interviews with class teachers it turns out there are some obstacles faced by teachers sometimes still difficult to civilize the character that has been implanted. This study aims to describe and analyze the social skills of elementary students in strengthening the implementation of character education. The research method used is qualitative research with descriptive approach. Techniques of collecting data using interviews, observation, and documentation. The data analysis used is interactive model analysis. The results showed that (1) students' social skills in integrated thematic learning as a whole is good, only the aspect of care for the environment that has not been maximized; (2) Implementation of character education is good, including planning, implementation, and evaluation carried out using five stages continuum; (3) There are supporting factors in the implementation of character are good figures, parent and good school communication, infrastructure, and extracurricular, while the inhibiting factors are the characteristics of different students, community environment, and the use of unattended gadgets